Comparison Analysis of Best First Search Algorithm with A * (star) in determining the closest route in the district Sleman - Tutik Maryana; Ripto Sudiyarno; Kusrini Kusrini (Universitas Raharja, 2020)
There are various pathfinding algorithms that have advantages and disadvantages of each algorithm. The purpose of this study is to compare the best-first search pathfinding greedy algorithm with A * (Star) in terms of determining the shortest route in a tent search. The method used in this study is an analytical method for analyzing what algorithms can be applied in track search. Then, the method continued with the design method for the best-first search and A * greedy algorithm, the user interface for the algorithm testing application. The next method is the implementation method, which is the best-first greedy algarithm search and A * implemented in the algorithm testing application. The last method is the method of testing algorithms that will be compared. The conclusions will be drawn from the results of comparison algorithms. The result of this study is the acquisition of a distance comparison between thegreedy best-first search algorithm with A *. The conclusion of this study is that the A * algorithm is able to provide the shortest and optimal route results compared to the BFS algorithm.